Tomato Production in Florida Using Fertigation Technology - Mary Dixon; Guodong Liu (EDIS)
Tomato is in high demand because of its taste and health benefits. In Florida, tomato is the number one vegetable crop in terms of both acreage and value. Because of its high value and wide acreage, it is important for tomato production to be efficient in its water and nutrient use, which may be improved through fertigation practices. Therefore, the objective of this new 7-page article is to disseminate research-based methods of tomato production utilizing fertigation to enhance yield and nutrient use efficiency. Written by Mary Dixon and Guodong Liu, and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1392